Strengthening community capability to solving the coastal erosion problem for sustainable development / การสร้างเสริมศักยภาพชุมชนในการแก้ไขปัญหาการกัดเซาะชายฝั่งเพื่อการพัฒนาอย่างยั่งยืน - ชเนตตี มิลินทางกูร, Chanettee Milintangul / (Journal of Community Development Research (Humanities and Social Sciences), 2014)
การสร้างเสริมศักยภาพชุมชนในการแก้ไขปัญหาการกัดเซาะชายฝั่งเพื่อการพัฒนาอย่างยั่งยืน มีวัตถุประสงค์เพื่อประเมินความพึงพอใจของชุมชนในการแก้ไขปัญหาการกัดเซาะชายฝั่งและการจัดการทรัพยากรชายฝั่ง รวมทั้งการส่งเสริมการมีส่วนร่วมของคนในชุมชน โดยเน้นการให้ความรู้แก่ชุมชนเพื่อเพิ่มศักยภาพให้ชุมชนมีส่วนร่วมในการร่วมคิด ร่วมวางแผน ร่วมทา ร่วมติดตาม และประเมินผลการดาเนินงานโครงการตั้งแต่เริ่มต้นจนเสร็จสิ้น โดยอาศัยแนวทางการบริหารจัดการแบบ Adaptive Management ซึ่งการดาเนินการดังกล่าวย่อมก่อให้เกิดการพัฒนาที่ยั่งยืน ผลจากการดาเนินโครงการ แสดงให้เห็นถึงศักยภาพของชุมชนในการมีส่วนร่วมในการตรวจติดตามและประเมินความสาเร็จในการแก้ไขปัญหาการ กัดเซาะชายฝั่ง รวมถึงการสร้างเสริมความรู้ความเข้าใจที่ชุมชนได้รับ มีส่วนอย่างยิ่งในการเพิ่มแรงบันดาลใจให้ชุมชน เห็นความสาคัญของการแก้ไขปัญหาด้วยตัวชุมชนเอง คำสำคัญ: ศักยภาพชุมชน การกัดเซาะชายฝั่ง การพัฒนาอย่างยั่งยืน This research project aims to strengthen the community capability in monitoring and evaluating the process of solving the coastal erosion problem, including community participation. This project focuses on community learning through participation in order to strengthen the community’s capability in planning, carrying out, monitoring, and evaluating the project from start to finish by Adaptive Management approach. This process would lead to sustainable development. The project outcome shows the community’s potential in monitoring and evaluating the process of solving the coastal erosion problem. Moreover, strengthening the community’s capability to participate is a key factor leading to the community’s inspiration to solve problems by themselves. Keywords: community capability, coastal erosion, sustainable development
Keywords: ศักยภาพชุมชน การกัดเซาะชายฝั่ง การพัฒนาอย่างยั่งยืน community capability, coastal erosion, sustainable development